2021
DOI: 10.1590/1678-7757-2020-0414
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of selenium against dental amalgam-induced intracellular oxidative toxicity through the TRPV1 channel in DBTRG glioblastoma cells

Abstract: The protective role of selenium against dental amalgam-induced intracellular oxidative toxicity through the TRPV1 channel in DBTRG glioblastoma cells Objective: The exposure to mercury (Hg) from dental amalgams is a suspected causative factor in neurological diseases. This study investigated the toxic effects of two different amalgam compositions related to Hg and the protective effects of selenium against the toxic effects of Hg through the TRPV1 channel in the human DBTRG glioblastoma cell line. Methodology:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Espaladori et al found that Se used for intracanal medication could potentiate the healing effects of calcium hydroxide in the anti-inflammatory response in periapical dental tissues [ 45 ]. According to Ceyan et al, Se demonstrated the protective effect against oxidative toxicity induced by dental amalgam [ 46 ].…”
Section: The Role Of Se In the Prevention And Treatment Of Health Dis...mentioning
confidence: 99%
“…Espaladori et al found that Se used for intracanal medication could potentiate the healing effects of calcium hydroxide in the anti-inflammatory response in periapical dental tissues [ 45 ]. According to Ceyan et al, Se demonstrated the protective effect against oxidative toxicity induced by dental amalgam [ 46 ].…”
Section: The Role Of Se In the Prevention And Treatment Of Health Dis...mentioning
confidence: 99%
“…In central nervous system (CNS) tumors, the cuprotosis-related gene dihydrolipoamide dehydrogenase (DLD) has been demonstrated to induce ferroptosis in head and neck cancer cells by regulating glutamine metabolism [ 12 ]. Copper may inhibit the activity of glioblastoma by impacting the processes of apoptosis and DNA damage repair in glioblastoma cells [ 13 ]. Moreover, copper complexes exhibit anti-tumor cell proliferation effects by modifying the oxidative-reductive state of glioma [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, with the con rmation of the speci c mechanism of cuprotosis, the perfect answer to the previous question about why copper inhibits the growth of tumors was given(8). For instance, copper inhibits the activity of glioblastoma cells because cuprotosis may be involved in the development of tumor cells (9). The fact that copper complexes can affect the redox state of gliomas to act as antiproliferative may also be due to the presence of cuprotosis in gliomas (10).…”
Section: Introductionmentioning
confidence: 99%